CORPORATE PERFORMANCE MEASUREMENT USING THE BALANCED SCORECARD: A CASE STUDY OF AN INDONESIAN FAST-FOOD FIRM - Naufal Dhenanda Aradea; Nuris Sanida (ZILLZELL MEDIA PRIMA, 2026)
Increasing competition in the fast-food industry requires companies to implement performance measurement systems that are not only financially oriented but also include non-financial aspects that influence business sustainability. Traditional performance measurement, which focuses solely on financial indicators, is considered insufficient to provide a comprehensive view of organizational performance. Therefore, this study applies the Balanced Scorecard method as a comprehensive performance measurement tool covering four perspectives: financial, customer, internal business processes, and learning and growth. This research aims to analyze the performance of PT Sari Burger Indonesia in Bandar Lampung based on the four Balanced Scorecard perspectives. The research method used is a quantitative approach with a descriptive research type. The data consist of primary data obtained through questionnaires distributed to 33 employees and 50 customers, as well as secondary data in the form of the company’s financial reports for the 2023–2024 period. The sampling technique used is simple random sampling. The results indicate that the overall performance of PT Sari Burger Indonesia falls into the fairly good category. The financial perspective shows relatively stable conditions, the customer perspective reflects a good level of satisfaction, internal business processes are running fairly effectively, and the learning and growth perspective indicates good employee satisfaction, although improvements are still needed in training and human resource development. Thus, the Balanced Scorecard is able to provide a comprehensive overview of company performance and can be used as a basis for strategic management evaluation.